Sukuk issuance for Meeting Basel III Capital Adequacy Requirements: a shariah analysis of Maybank Tier 1 sukuk - Bello, Nabil; Hasan, Aznan (2018)
The purpose of this paper is to examine sukuk structures as a regulatory capital instrument for meeting Additional Tier 1 (AT1) capital under Basel III capital adequacy requirements and the Bank Negara Malaysia framework. The most important issues examined are the Shariah issues underlying the sukuk structures such as the subordination in structuring equity-based sukuk. As a case study, the Maybank AT1 sukuk issued in December 2017 based on wakalah bi al-istithmar sukuk was analysed. Data was collected from the documents related to the sukuk and analysed the contents thematically. The study finds that the Shariah principle in the sukuk, even though called wakalah bi al-istithmar sukuk, possesses more of a musharakah structure. The study is the first known study that examines the wakalah bi al-istithmar sukuk and particularly the Maybank AT1 sukuk for meeting Basel III capital requirements. The study will serve as an important reference for structuring sukuk for meeting capital requirements